Impact of Climate Change on Soil Hydro-Climatic Conditions and Base Cations Weathering Rates in Forested Watersheds in Eastern Canada - Houle, Daniel; Marty, Charles; Augustin, Fougère; Dermont, Gérald; Gagnon, Christian (Frontiers in Forests and Global Change, 2020)
Increases in mean annual air temperature (MAAT) and mean annual precipitation (MAP) are projected for north eastern North America, which will alter soil hydro-climatic conditions and hence the rate of many soil processes. Among them, chemical weathering of soil minerals is an essential source of base cations (BC) which control the acid-base status of surface waters and are crucial for forest nutrition. In this modeling study, MAAT and MAP projections from a regional and a global climate models were first used to project changes in soil temperature (MAST) and soil water content (SWC) with the ForStem and ForHym models for 21 eastern Canadian forested catchments. The models predicted an increase in MAST by 2.03-2.05°C and 2.87-3.42°C for the 2041-2070 and 2071-2100 periods, respectively, and small decreases (<5%) in SWC. In a second step, these projected changes in MAST and SWC were used to estimate changes in BC weathering rates (WR) and soil pH with the geochemical model PROFILE. The simulations indicated that BC WR would increase by 13-15% and 20-22% for the 2041-2070 and 2071-2100 periods, respectively. The increase in BC WR was accompanied by an increase not only in base cation concentrations, but also in soil pH at most sites, suggesting that future temperature increase has the potential to ameliorate the acid-base status and the fertility of soils in eastern Canada through its impact on WR.